Soil management in Lepidium meyenii (maca) monoculture: trends and challenges for small farmers around Lake Chinchaycocha in the Andean highlands of Junin (Peru) - Solórzano-Acosta, Richard; Chanco, Mirella; Seminario, Martín; Cabello-Torres, Rita; Camel, Vladimir; Lastra, Sphyros; Arias, Alberto; Verástegui, Patricia; Quispe, Kenyi; Carbajal-Llosa, Carlos; Cuevas, Juan Pablo; Cruz, Juancarlos; et al. (Frontiers in Soil Science, 2025)
IntroductionMonoculture is a significant concern due to its negative impact on soil quality, resource productivity, and agricultural sustainability, particularly in vulnerable communities. This research aims to evaluate high Andean soil management for maca monoculture.Materials and methodsTo this end, interviews were conducted with maca farmers adjacent to Lake Chinchaycocha. The effect on soil quality was evaluated based on principal component analysis (PCA), weighted soil quality index (SQIw), and physico-chemical characteristics.ResultsThe results indicated differences between farmers in agronomic management, monoculture period (from 5 to 9 years), and fallow time (up to 10 years in the best cases). Regarding soil quality, the PCA highlighted boron and total nitrogen locations in the same quadrant, with the highest contribution to the analysis. Finally, the SQIw showed that soils without maca cultivation presented better quality.ConclusionThis research’s results indicate a need to optimize soil management practices, especially for small farmers, who are the most vulnerable group. In addition, further studies on boron and nitrogen availability in soils cultivated with maca are required, emphasizing areas that exceed 10 years of continuous use.